2017
DOI: 10.1007/s12035-017-0597-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Brain-Derived Neurotrophic Factor Transcripts I and VI, cAMP Response Element Binding, and Glucocorticoid Receptor in the Cortex of Patients with Temporal Lobe Epilepsy

Abstract: A body of evidence supports a relevant role of brain-derived neurotrophic factor (BDNF) in temporal lobe epilepsy (TLE). Magnetic resonance data reveal that the cerebral atrophy extends to regions that are functionally and anatomically connected with the hippocampus, especially the temporal cortex. We previously reported an increased expression of BDNF messenger for the exon VI in the hippocampus of temporal lobe epilepsy patients compared to an autopsy control group. Altered levels of this particular transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 83 publications
0
25
0
4
Order By: Relevance
“…Increased levels of BDNF have been reported in brain pathologies, although little is known about their role in the pathophysiology of neurometabolic diseases. In this context, a recent study reported an increased expression of BDNF transcripts I and VI in cerebral cortex of patients with temporal lobe epilepsy (Martinez‐Levy et al, ). This increase was related to the high demand for plasticity readjustments required to recover the brain tissue from the damage caused by persistent seizures, similar to the increase in BDNF protein levels measured in brain cortex samples of epileptic patients (Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Increased levels of BDNF have been reported in brain pathologies, although little is known about their role in the pathophysiology of neurometabolic diseases. In this context, a recent study reported an increased expression of BDNF transcripts I and VI in cerebral cortex of patients with temporal lobe epilepsy (Martinez‐Levy et al, ). This increase was related to the high demand for plasticity readjustments required to recover the brain tissue from the damage caused by persistent seizures, similar to the increase in BDNF protein levels measured in brain cortex samples of epileptic patients (Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Martínez-Levy et al and de Souza Bernardino et al found an increased expression of BDNF transcription in patients with epilepsy, which also supported the idea that the high expression of BDNF in some brain areas may contribute to limbic seizures. 34 , 35 Moreover, transgenic mice with high expression of BDNF also indicated an increased seizure risk combined with a hippocampal hyperexcitability. 13 This cumulative evidence prompted the idea that the abnormalities in the BDNF gene may be responsible for epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Одной из наиболее частых причин развития височной эпилепсии является склероз гиппокампа, что нередко предопределяет необходимость хирургического вмешательства [1][2]. Показано, что трансформация нормального паттерна активности нейронов в пароксизмальный сопровождается изменениями экспрессии цитокинов в гиппокампе и височной коре головного мозга, в том числе интерлейкина (ИЛ) 1β и нейротрофического фактора мозга (Brain-Derived Neurotrophic Factor, BDNF), связанного с мембранно-ассоциированным тирозинкиназным рецептором В, кодируемым геном NTRK2 [3][4].…”
Section: Temporal Lobe Epilepsy (Tle) Is One Of the Most Common And Runclassified
“…Особое внимание в развитии височной эпилепсии уделяют BDNF -нейротрофину, способствующему росту, выживанию и дифференциации нейронов, а также синаптической пластичности в различных регионах мозга, особенно в гиппокампе. Так, показана повышенная экспрессия BDNF в гиппокампе, височной коре во время приступов у пациентов с фармакорезистентными формами эпилепсии [4]. ОНП rs6265 гена BDNF представляет собой функцио-нально релевантный полиморфизм, который ассоциирован с секрецией BDNF и объемом гиппокампа [11].…”
Section: Temporal Lobe Epilepsy (Tle) Is One Of the Most Common And Runclassified
See 1 more Smart Citation